2017
DOI: 10.1111/1744-7917.12443
|View full text |Cite
|
Sign up to set email alerts
|

Identification and comparison of long non‐coding RNAs in the silk gland between domestic and wild silkworms

Abstract: Under long-term artificial selection, the domestic silkworm (Bombyx mori) has increased its silk yield tremendously in comparison with its wild progenitor, Bombyx mandarina. However, the molecular mechanism of silk yield increase is still unknown. Comparative analysis of long non-coding RNAs (lncRNAs) may provide some insights into understanding this phenotypic variation. In this study, using RNA sequencing technology data of silk gland in domestic and wild silkworms, we identified 599 lncRNAs in the silk glan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 63 publications
(122 reference statements)
5
18
0
Order By: Relevance
“…Apart from more "factories" for silk fibroins production, our results revealed that in the late stage of silk gland development, the up-regulated genes in the domestic silkworm are enriched in protein processing in the endoplasmic reticulum and ribosome pathways (Figure 2A and Supplementary Figure S4A), indicating that protein synthesis is more active in the domestic silkworm. These results are consistent with previous studies (Fang et al, 2015;Li J. Y. et al, 2017;Zhou et al, 2018).…”
Section: Discussionsupporting
confidence: 94%
“…Apart from more "factories" for silk fibroins production, our results revealed that in the late stage of silk gland development, the up-regulated genes in the domestic silkworm are enriched in protein processing in the endoplasmic reticulum and ribosome pathways (Figure 2A and Supplementary Figure S4A), indicating that protein synthesis is more active in the domestic silkworm. These results are consistent with previous studies (Fang et al, 2015;Li J. Y. et al, 2017;Zhou et al, 2018).…”
Section: Discussionsupporting
confidence: 94%
“…indicating that protein synthesis is more active in the domestic silkworm than wild silkworm. These results are consistent with previous studies [18,19,26].…”
Section: Discussionsupporting
confidence: 94%
“…We further explored the potential regulatory functions of lncRNAs on the development of PSGs and the biosynthesis of fibroin. Our current study indicated that the function of the silkworm lncRNAs is not only related to fibroin synthesis and apoptosis of silk glands as stated in the previous studies (Wu et al, 2016;Zhou et al, 2018;Chen et al, 2019), but also promote the degradation of silk proteins by regulating RNA/amino acid degradation, the proteasome and proteolysis. Moreover, lncRNA may participate in nucleotide excision repair, heat shock proteins expression, autophagy activation and endoplasmic reticulum stress response to maintain the homeostasis of the PSG cells.…”
Section: Introductionsupporting
confidence: 77%
“…The scoring thresholds for the three software programs were as follows: CPC, 0 (transcripts with a value >0 were considered mRNAs, and those with a value <0 were considered lncRNAs); CNCI, 0 (transcripts with a value >0 were considered mRNAs, and those with a value <0 were considered lncRNAs); and txCdsPredict, 500 (transcripts with a value >500 were considered mRNAs, while those with a value <500 were considered lncRNAs). All predicted lncRNAs were aligned to lncRNAs collected in BmncRNAdb and previous study (Wu et al, 2016;Zhou et al, 2018). We introduced NCBI Blast tool for the comparison which was based on sequence similarity (Parameters: blastall -e 1e-5 -p blastn -a 8 -d xx.fa -i xx.fa -o blast).…”
Section: Sequence Analysis and Lncrna Identificationmentioning
confidence: 99%
See 1 more Smart Citation